HEPATO-PROTECTIVE ROLE OF THE AQUEOUS AND N-HEXANE EXTRACTS OF NIGELLA SATIVA LINN. IN EXPERIMENTAL LIVER DAMAGE IN RATS - Yesmin, Farida; Rahman, Zaida; Dewan, Jesmin Fouzia; Helali, Asadul Mazid; A Rahman, Nor Iza; Alattraqchi, Ahmed G.; Ahmed, Arefuddin; Yousuf, Rabeya; Salam, Abdus; Haque, Mainul (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective: Liver disease is associated with the formation of oxygen derived free radicals. Reactive oxygen species (ROS) as well as nitrogen species are responsible for nuclear DNA fragmentation and cell death. Active principle of thymoquinone (TQ) of Nigella sativa acts as a scavenger of superoxide anion. Current study was conducted to evaluate the hepatoprotective effect of Nigella sativa on rats. Methods: The study was carried out at prime postgraduate medical University of Bangladesh. Liver damage and oxidative stress were evaluated by measuring serum alanine amino transferase (ALT), hepatic malondialdehyde (MDA) and hepatic Glutathione (GSH) levels. Aqueous extract of Nigella sativa and n-hexane extract of Nigella sativa were administered orally into two groups' of rats through intra-gastric tube for 28 days. Both the groups received paracetamol intraperitoneally on day 28th and were sacrificed on day 30th. Subsequently, the following parameters were studied: Serum ALT, hepatic MDA, and hepatic GSH. Results: Hepatic damage was evaluated by significant increases in serum ALT (p<0.001) and hepatic MDA (p<0.001) concentration with depleted hepatic GSH (p<0.001) in paracetamol treated group. Pre-treated with aqueous extract of Nigella sativa significantly reduced serum ALT (p<0.001) and hepatic MDA (p<0.001) levels and also significantly associated with the increase in hepatic GSH (p<0.01). Pretreatment with n-hexane extracts of Nigella sativa decreased serum ALT (p<0.001), hepatic MDA (p<0.001) and increased hepatic GSH (p<0.001). Conclusion: Hepatoprotective properties of Nigella sativa in liver damage of experimental rats by reducing oxidative stress is evident. Protection afforded by the n-hexane extract of Nigella Sativa in pre-treated group has also been validated. KEY WORDS: Hepatoprotective, Liver-damage, Nigella sativa Linn.